Pegadaan Perpustakaan Desa sebagai Wadah Pengembangan Literasi Masyarakat - Sam’un, Ahmad; Agus Muzakki; Puspita Dewi; Fathurrahman (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2025)
The establishment of a village library is part of the 45-day KKN (Community Service Program) by UNIQHBA Bagu students. The goal of this library is to provide facilities and a platform to foster the literacy interest of the community in Buwun Mas Village, Sekotong Subdistrict, West Lombok. This program is carried out in several stages, namely planning, implementation, and evaluation. The planning stage includes interviewing the community, observing the village, and preparing and evaluating the work program plan. The implementation of the Village Library Establishment as a Platform for Community Literacy Development is conducted in three stages: 1) Coordination of the library location, “Bale Literasi,” through discussions with the village government, community leaders of Buwun Mas Village, and observations of recommended locations, which took place from September 1, 2024, to September 7, 2024. 2) Acquisition of reading materials through a book donation program, which ran from September 3, 2024, to October 5, 2024, and the submission of a book aid proposal on September 10, 2024. 3) Arrangement of the Bale Literasi Village Library space, including the creation of bookshelves and adding accessories to beautify the library, which took place from September 16, 2024, to September 21, 2024.